Extending thermotolerance to tomato seedlings by inoculation with SA1 isolate of Bacillus cereus and comparison with exogenous humic acid application - Khan, Muhammad Aaqil; Asaf, Sajjad; Khan, Abdul Latif; Jan, Rahmatullah; Kang, Sang-Mo; Kim, Kyung-Min; Lee, In-Jung (PloS one, 2020)
Heat stress is one of the major abiotic stresses that impair plant growth and crop productivity. Plant growth-promoting endophytic bacteria (PGPEB) and humic acid (HA) are used as bio-stimulants and ecofriendly approaches to improve agriculture crop production and counteract the negative effects of heat stress. Current study aimed to analyze the effect of thermotolerant SA1 an isolate of Bacillus cereus and HA on tomato seedlings. The results showed that combine application of SA1+HA significantly improved the biomass and chlorophyll fluorescence of tomato plants under normal and heat stress conditions. Heat stress increased abscisic acid (ABA) and reduced salicylic acid (SA) content; however, combined application of SA1+HA markedly reduced ABA and increased SA. Antioxidant enzymes activities revealed that SA1 and HA treated plants exhibited increased levels of ascorbate peroxidase (APX), superoxide dismutase (SOD), and reduced glutathione (GSH). In addition, heat stress markedly reduced the amino acid contents; however, the amino acids were increased with co-application of SA1+HA. Similarly, inductively-coupled plasma mass-spectrometry results showed that plants treated with SA1+HA exhibited significantly higher iron (Fe+), phosphorus (P), and potassium (K+) uptake during heat stress. Heat stress increased the relative expression of SlWRKY33b and autophagy-related (SlATG5) genes, whereas co-application of SA1+HA augmented the heat stress response and reduced SlWRKY33b and SlATG5 expression. The heat stress-responsive transcription factor (SlHsfA1a) and high-affinity potassium transporter (SlHKT1) were upregulated in SA1+HA-treated plants. In conclusion, current findings suggest that co-application with SA1+HA can be used for the mitigation of heat stress damage in tomato plants and can be commercialized as a biofertilizer.